2022
DOI: 10.1039/d1ra05717k
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide-incorporated calcium phosphate cements with pulsed electromagnetic fields for bone regeneration

Abstract: Natural calcium phosphate cements (CPCs) derived from sintered animal bone have been investigated to treat bone defects, but their low mechanical strength remains a critical limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…At the highest dose of 1000 µg/mL after incubation for 24 h, the treatment with T-rGO reduces cell viability by up to 19.34%, while with GO, the cell mortality was enhanced, reaching 21.69%. According to Akhavan et al, both size and concentration of graphene-based materials were found to have harmful effects on human mesenchymal stem cells [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the highest dose of 1000 µg/mL after incubation for 24 h, the treatment with T-rGO reduces cell viability by up to 19.34%, while with GO, the cell mortality was enhanced, reaching 21.69%. According to Akhavan et al, both size and concentration of graphene-based materials were found to have harmful effects on human mesenchymal stem cells [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it was reported that by activating caspase 8 and caspase 3, the in vivo study found that daunorubicin-loaded graphene–gold nanocomposites caused apoptosis and inhibited the growth of multidrug-resistant leukemia cells [ 37 ]. The graphene-based materials caused DNA fragmentation in cancer cells [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The microcurrent generated by PEMF irradiation can affect cells [33]. This combined application of rGO and PEMF for osteogenesis has been reported previously that can promote osteogenic differentiation ability with more calcium deposition [34] but has rarely been combined for the repair of peripheral nerve defects.…”
Section: Introductionmentioning
confidence: 91%
“…In addition to the contribution of gel on CPC mechanical properties, gel also improves cement biocompatibility. [10,13] Despite the improvement in CPC performance imparted by incorporating these polymers, further enhancements are still needed to heighten CPC osteogenic capabilities [8,14] for deployment in clinical bone augmentation procedures. [15] Many materials have been suggested as cement additives to enhance the osteogenic ability of CPCs.…”
mentioning
confidence: 99%
“…Additionally, recent studies revealed that CPCs loaded with magnetic nanoparticles and primed with electromagnetic fields enhanced osteogenic differentiation of human dental pulp stem cells and rat adipose-derived stem cells. [14,23] Despite the many strategies investigated for improving the osteogenic potential of CPCs, demonstrated efficacy of these new methods in clinical bone reconstruction procedures has remained elusive.…”
mentioning
confidence: 99%